Coady, Amanda. South Side Cape Broyle, Tom Coady Property. L to R, Nicky Boland, Tom Coady, Don Coady, Tom Boland. - Heritage NL
Amanda Coady provided a picture of (from left to right) Nicky Boland (partially obscurred), Tom Coady, Don Coady and Tom Boland. Nicky is partially visible looking at the image's other subjects in the bottom left corner of the image. Tom Coady and Don Coady sit next to each other on what appears to be a cot with three large windows behind them. Don is holding an accordian in his hands, balancing it on his knees, with a beer by his feet. Tom Boland sits on a wooden chair beside the cot holding a beer in his hands with the curtains for the window behind him. A rocing chair is visible in the next room through the doorway immediately to the right of Tom Boland.